2020
DOI: 10.3390/su12051907
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-Metal Pollution Characteristics and Influencing Factors in Agricultural Soils: Evidence from Shuozhou City, Shanxi Province, China

Abstract: Although soil quality can be highly altered by mining activities, there are few reports on soil pollution in mining cities. We systematically characterized the heavy metals (HMs) pollution, risks, sources, and influencing factors in the surrounding soils of Shuozhou. Specifically, 146 samples were collected, and the potential ecological risk index (RI) and the single-factor index were jointly used to understand the environmental risk of HMs. Meanwhile, correlation analysis was applied to find the influencing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
0
8
1
Order By: Relevance
“…Correlation analysis is a commonly used method to determine the sources and pathways of heavy metals [25][26][27]. Generally, heavy metals with a high correlation coefficient may have similar sources or experience the same migration and transformation process.…”
Section: Multivariate Statistical Results and Their Implications For Sourcesmentioning
confidence: 99%
“…Correlation analysis is a commonly used method to determine the sources and pathways of heavy metals [25][26][27]. Generally, heavy metals with a high correlation coefficient may have similar sources or experience the same migration and transformation process.…”
Section: Multivariate Statistical Results and Their Implications For Sourcesmentioning
confidence: 99%
“…Some authors compared the concentration values of the same soil, before and after the presence of anthropological sources. They demonstrated that an increase of concentration was precisely due to these activities [8]. In agricultural soils, high concentrations are due to the use of fertilizers and pesticides [29].…”
Section: Presence and Distribution Into The Environmentmentioning
confidence: 99%
“…The forest landscape is composed of forest ecosystems as the main body [1]. Due to the joint action of a variety of ecological processes (such as long-term mining activities, serious soil erosion, and a series of ecological restoration projects), which have a significant impact on landscape function, process, formation, and structure [2][3][4], the forest landscape of the Fenhe River Basin in China changes frequently and has a high degree of temporal and spatial heterogeneity [5][6][7]. The fragmentation, degradation, and loss of forest landscape caused by disturbance may threaten many ecosystems and processes [8] and even limit the diffusion of some species in the ecosystem [9].…”
Section: Introductionmentioning
confidence: 99%